The germ of the Peruvian wart - Hercelles, Oswaldo (1926)
Early laboratory work aimed at exclarecer Peruvian wart problem, started in 1897 by a group of medical students, among which occupies a prominent place loc Alberto Barton; enough to review publications in that year were to agree that that was the era of National Medicine, where he worked with great enthusiasm po lift the veil that hid Carrion's disease.